Application of Knowledge Management in Health Worker Decision Making at Main Clinic "X" in Tenggarong - Safitri, Novia; Rinawati, Rinawati (Jurnal Indonesia Sosial Sains, 2025)
This study discusses the application of knowledge management in decision-making of health workers at the Main "X" Clinic in Tenggarong with a focus on the integration of Electronic Medical Records (RME). The research background departs from the importance of fast, accurate, and evidence-based clinical decisions in the midst of limited resources and workloads of health workers. This study uses a qualitative descriptive approach with informants of nurses, doctors, midwives, heads of clinics, and RME administrative officers; data were collected through semi-structured interviews, observations, and documentation (SOP, RME, reports); The analysis was performed using the Miles & Huberman model. Results show that knowledge management is implemented through case discussions, briefings, training, and structured clinical documentation, while RME serves as a repository of knowledge that facilitates access to patient histories and supports standardization of records. The integration of knowledge management and RME has been proven to strengthen clinical decision-making processes, improve speed, accuracy, and consistency of decisions, although there are still obstacles such as suboptimal utilization of RME features, variations in digital capabilities, and high workloads.